PENGARUH MODEL BERBASIS PjBL BERBANTUAN MEDIA AUDIO VISUAL TERHADAP KETERAMPILAN MEMPRODUKSI TEKS EKSPLANASI - Bunga Febrimora Hendri (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2021)
This study I am as to :1) descript the skills of producing explanatory text with PjBL assisted be audio visual media. 2) descript the skill to producing explanatory the text after the aplication of the PjBL model assisted by audio visual media. 3) analyzing the effect of the application of the PjBL model assisted by audio visual media on the skills of producing explanatory text. This type of research is a quantitative study using descriptive analytical methods with a pre test and posttest one group design.Population in this study were grade VIII students of SMPN 15 Padang registered in 2019, totaling 117 students. The sample of this study were studentsin grade VIII totalling 30 students and the sampling in this study wash using purposive sampling technique. Result and discussion : 1) the skill of producing explanatory text before applying the PjBL model assisted by audiovisual media is in the range of values of 51,57 with almost sufficient qualifications. 2) the skill of producing explanatory text after the application of the PjBL model assisted by audiovisual media is in the range of values 81,13 with good qualifications. 3) based on the result of hypothesis testing, it can be concluded that there is an effect of the skill of producing explanatory text for grade VIII students of SMP N 15 Padang before and after the application of the PjBL model assisted by audio visual media at a significant level of 0.95 with degrees of freedom n-1 (30-1=29)